Psychometric Analysis Instruments of Self-efficacy in Work - Amalianingsih, Restu; Herdi (Bisma The Journal of Counseling, 2022)
The purpose of this study was to determine the Self-efficacy of students in their ability to achieve a certain level in the context of work. Respondents in this study were 234 students of class XII Vocational High School in Tangerang City. The sampling technique used in this research is non-probability sampling with the snowball sampling method. Researchers distributed online questionnaires through Google Forms to student representatives from several class XII Vocational High School in various schools. The instrument used in this study was the Work Self-efficacy Scale (WSES). This scale consists of a total of 10 items with 2 dimensions, namely Relational Willingness and Commitment. The results of the study, this Work Self-efficacy instrument can be declared reliable and valid. It is said to be reliable or consistent because in the third test, the calculation results obtained a Cronbach alpha reliability coefficient value of 0.874. The coefficient value is greater than the standard parameter, namely 0.7. This means that this instrument can be used repeatedly and can produce a consistent picture of Work Self-efficacy.